2015
DOI: 10.1016/j.ophtha.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial and Clinical Outcomes of Orbital Decompression Surgery for Thyroid Eye Disease and Predictors of Change in Quality of Life

Abstract: This study highlights the importance of appearance-related cognitions in predicting quality of life outcomes after surgery. Implications for clinical practice need to be considered in light of the limitations of this study, but it is suggested that psychosocial interventions targeting appearance-related cognitive processes, in particular personal evaluation of appearance, could enhance the quality of life outcomes for patients with TED undergoing orbital decompression surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…We think that is a main reason why there is a large difference regarding incomplete data for the two groups. Wickwar S et al 26. reported that the appearance-related social anxiety and avoidance caused by surgery were all found to improve as time goes on, suggesting that the HRQoL of patients take some time to change after OT.…”
Section: Discussionmentioning
confidence: 99%
“…We think that is a main reason why there is a large difference regarding incomplete data for the two groups. Wickwar S et al 26. reported that the appearance-related social anxiety and avoidance caused by surgery were all found to improve as time goes on, suggesting that the HRQoL of patients take some time to change after OT.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the group of Yue, who assessed HRQoL, showed that it significantly improved after 6 months from both surgery and RFA, but that patients who had been treated with RFA had better HRQoL as compared to those surgically treated. Nevertheless, the same authors argued that these differences could have disappeared over time, as HRQoL of patients that are operated on take some time to convalesce after surgery [36].…”
Section: Discussionmentioning
confidence: 99%
“…28 After an orbital decompression, the improvements in QOL are most related to visual function and appearance. 29,30 The overall complication rate after orbital decompression is 9.3%. 31 Immediate complications include periorbital ecchymosis and edema, postoperative hemorrhage, and infection.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%